Verifikasi dan Validasi Risiko Stunting sebagai Inisiatif Pencegahan Dini di Desa Mertoyudan - Anggarini, Yunita; Aryasani, Wisnu; Chrishanty Lesilolo, Gracella Meylinda; Abdullah, Fauzaan Rafi Putra; Novitasari, Fitri; Taskia, Hilda Taskia Hilda; Irawati, Ika; Risadi, Husain; Yansaputra, Hardi; Setyawan, Hakiki; Utami, Retnasih Tri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Stunting remains a crucial health challenge in Indonesia, requiring accurate data for effective intervention. The Community Service Program (KKN) in Mertoyudan Village aimed to verify and validate data to obtain accurate information on families at risk of stunting as an early preventative measure. The methods employed included door-to-door surveys, in-depth interviews with caregivers, and data synchronization with village records. The results revealed unrecorded risk factors and inconsistencies in legacy data, while also raising community awareness of the importance of monitoring child nutrition. Conclusion: A collaborative approach between students and the village government is crucial for improving local data quality. These results demonstrate that direct field validation is key to the success of early detection strategies and the accuracy of targeting stunting prevention programs in rural areas.